Peak torque, reaction time, and rate of torque development of hip abductors and adductors of older women - Morcelli, Mary Hellen [UNESP]; Rossi, Denise Martineli; Karuka, Aline Harumi [UNESP]; Crozara, Luciano Fernandes [UNESP]; Hallal, Camilla Zamfolini; Marques, Nise Ribeiro [UNESP]; Goncalves, Mauro [UNESP]; Navega, Marcelo Tavella [UNESP] (Taylor & Francis Inc, 2016)
Impaired muscle function at the hip has been implicated to be a major factor related to falls in older adults. Therefore, the aim of this study was to analyze the rate of torque development (RTD), reaction time (RT), and peak torque (PT) of hip abductors and hip adductors in young women (YW), older women nonfallers (ONF), and older women fallers (OF). Eighteen YW and 44 older women divided among OF (n = 20) and ONF (n = 24) performed maximum isometric hip abductor and adduction contractions on a dynamometer. YW had 40% greater PT and 61.5% greater RTD for hip abductors than the ONF. Compared with OF, YW had 47.5% greater PT and 68% greater RTD. OF showed less RTD at 150 ms (31%) and 200 ms (34.5%) than ONF for hip abductors. PT of hip adductors was 52% greater in YW than in the two older groups, whereas RTD was 71% greater. OF showed less RTD than ONF for hip abductors according to standardized effect sizes. No RT differences were observed between the three groups. We conclude that older women (OF and ONF) have less strength and ability to develop force rapidly than YW for hip abductors and adductors. Low hip strength and slowed force development in ONF during hip abduction may increase fall risk in older women.
Keywords: Accidental falls; aged; dynamometer; hip; muscle strength